Secondary headaches - red and green flags and their significance for diagnostics - Tissa Wijeratne; Chanith Wijeratne; Nadja Korajkic; Stefanie Bird; Carmela Sales; Franz Riederer (eNeurologicalSci, 2023)
A small percentage of patients suffer from a secondary headache syndrome. It is imperative that clinicians are able to differentiate primary headache syndromes from secondary headache syndromes, as failure to do so significantly worsens morbidity and mortality. Recent advances in our understanding of pathobiological mechanisms offer useful information on these enigmatic disorders. We now understand that the causes of secondary headache syndromes can vary significantly – these may be infectious, inflammatory, vascular, traumatic or structural in origin.A well-taken history and targeted physical examination coupled with appropriate investigations can enable these syndromes to be recognized consistently and thus allow their timely and appropriate treatment. Along with their epidemiology, some of their key characteristics shall thus be discussed in this review so as to aid the busy clinician at the bedside. Red flags including sudden onset, high pain intensity, pattern of change of a preexisting headache, focal neurological signs or seizure, systemic signs and precipitation by physical activity can guide the clinician to suspect a secondary headache. Importantly a preexisting headache is not an exclusion of a secondary headache – it might even be a predisposition in certain cases.